2021
DOI: 10.2139/ssrn.3881525
|View full text |Cite
|
Sign up to set email alerts
|

Inflation During the Pandemic: What Happened? What is Next?

Abstract: We analyze the evolution and drivers of inflation during the pandemic and the likely trajectory of inflation in the near-term using an event study of inflation around global recessions and a factor-augmented vector auto-regression (FAVAR) model. We report three main results. First, the decline in global inflation during the 2020 global recession was the most muted and shortest-lived of any of the five global recessions over the past 50 years and the increase in inflation since May 2020 has been the fastest. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
(26 reference statements)
1
8
0
Order By: Relevance
“…In the case of inflation, the historical decomposition shows that demand and supply shocks countered each other during COVID-19 dampening the decline in inflation, similar to the finding by Ha et al (2021). The relatively larger role of demand also occurs in the case of inflation and, as a consequence, annual inflation fell from 2 percent on an annual basis in the first quarter of 2020 to 0.7 percent in the second quarter and rebounded quickly.…”
Section: Decomposing Supply and Demand Factors In Output And Inflatio...supporting
confidence: 62%
“…In the case of inflation, the historical decomposition shows that demand and supply shocks countered each other during COVID-19 dampening the decline in inflation, similar to the finding by Ha et al (2021). The relatively larger role of demand also occurs in the case of inflation and, as a consequence, annual inflation fell from 2 percent on an annual basis in the first quarter of 2020 to 0.7 percent in the second quarter and rebounded quickly.…”
Section: Decomposing Supply and Demand Factors In Output And Inflatio...supporting
confidence: 62%
“…The outbreak of a large-scale pandemic causes oil prices to plummet as the embargo disrupts transport and travel, which account for two-thirds of global energy consumption [7]. For oil-exporting countries, a significant drop in the price of oil can have a severe impact on the volume of their exports and fiscal revenues, and governments may reduce government spending as a result.…”
Section: Energy Pricementioning
confidence: 99%
“…As mass pandemic outbreaks and embargoes have led to a surge in unemployment, at least 40 countries have adopted the policy of 'temporary wage subsidies' as a means of mitigating the effects of the economic crisis. Blanchard notes that rising inflation and tight labour markets may prompt workers to demand nominal wage increases to catch up with or even exceed inflation, creating a wage-price spiral [7].…”
Section: Wage Subsidies During the Crisismentioning
confidence: 99%
“…They detect that Global Value Chain (GVC) has a significant effect on transmitting supply chain disruptions from most countries that have been unprecedented. Ha et al (2021) investigated consumer price change forces, focusing on the COVID‐19 pandemic in developed and developing countries. Their results reported that supply chain disruptions are the most considerable force in increasing the current inflation.…”
Section: Literature Reviewmentioning
confidence: 99%